Laos - Dalal, A. Kamala (Washington, D.C. : National Geographic, 2009)
Photographs, maps, and illustrated text explore the geography, people, history, culture, and government of Laos.
Map on endpaper.
Includes bibliographical references (p. 61) and index.
6.8
5-8
Keywords: Laos -- Juvenile literature; Laos; Laos